HIGH-PRESSURE RAMAN SPECTROSCOPIC STUDY OF CO- AND NI-OLIVINES - Lin C.C. (My University, 2001)
The Raman spectra of synthetic α-Co2SiO4 and α-Ni2SiO4 olivines have been studied at room temperature and various pressures. All the Raman frequencies of the two olivines increase with increasing pressure, and most of the frequency–pressure plots obtained under both quasi- and nonhydrostatic conditions are nonlinear. It has been found that the average pressure derivative of Raman frequencies of the lattice modes in both Co- and Ni-olivines is smaller than that of the internal modes of SiO4, indicating that the distortion of SiO4 tetrahedra under static compression may be more severe than that of MO6 octahedra. In addition, four new Raman bands were observed in Ni-olivine under nonhydrostatic compression and above 30 GPa. This result suggests that a new phase of Ni-olivine should be formed at 30 GPa or amorphization may occur at still higher pressure.